Dedifferentiation of esophageal progenitors in metaplasia and cancer. (2nd November 2021) - Vercauteren Drubbel, Alizée; Beck, Benjamin
ABSTRACT: Barrett syndrome is a squamo-columnar metaplasia increasing the risk of developing esophageal adenocarcinoma. Recently, we showed that esophageal cells can transdifferentiate into undifferentiated columnar cells in vivo . Here, we discuss about the potential of these cells to be a reservoir for intestinal metaplasia and/or esophageal adenocarcinoma.